Mental Skill Usage of Athletes with Physical Disabilities - Ferhat Esatbeyoğlu; Mark Campbell (Türk Spor ve Egzersiz Dergisi)
Mental skills training strategies should be beneficial for a variety of different skills, age groups and special populations. The purpose of the present research were twofold; initially to examine performance strategies in various sport situations used by volleyball, sitting volleyball and amputee soccer players, and comparing it among the sports; and secondly, whether the current performance level of athletes and the years participating in sport would show a significant difference in their application o f psychological skills during practice and competition. The refined version of Test of Performance Strategies (TOPS) was administrated to athletes (N=309) competing across a range of performance standards in volleyball, sitting volleyball and amputee soccer sports. Results revealed that, relative to competition strategies, participants scored highest on activation and lowest on relaxation (4.10±0.52; 3.03±0=1.04, respectively) and in practice environment they scored highest on self-talk and lowest on relaxation (3.84±0=.91; 2.80±0.98, respectively). Examination of the results showed moderately strong correlations among many of the strategies in both competition and practice environments (P lt;0.01). Additionally, comparison of mental skills and strategies usage according to sports, discovered significant sport specific variations both in competition and practice settings (P lt;0.01). Investigation of current performance level differences in psychological skills and strategies explored differences among international, national and club level athletes (P lt;0.01). Exploration of years participating in sport comparison has also discovered differences among groups (P lt;0.01). These findings provide a unique insight into the mental skill usage of athletes with physical disabilities and their application to practise and environment settings.